1999
DOI: 10.1016/s0896-6273(00)80681-9
|View full text |Cite
|
Sign up to set email alerts
|

Prior Exposure to Neurotrophins Blocks Inhibition of Axonal Regeneration by MAG and Myelin via a cAMP-Dependent Mechanism

Abstract: MAG is a potent inhibitor of axonal regeneration. Here, inhibition by MAG, and myelin in general, is blocked if neurons are exposed to neurotrophins before encountering the inhibitor; priming cerebellar neurons with BDNF or GDNF, but not NGF, or priming DRG neurons with any of these neurotrophins blocks inhibition by MAG/myelin. Dibutyryl cAMP also overcomes inhibition by MAG/myelin, and cAMP is elevated by neurotrophins. A PKA inhibitor present during priming abrogates the block of inhibition. Finally, if neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
377
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 492 publications
(396 citation statements)
references
References 58 publications
16
377
1
Order By: Relevance
“…It was shown that inhibition of G i /G o with PERTUSSIS TOXIN blocked myelin-induced growth cone collapse 67 . We, on the other hand, reported that pertussis toxin had no effect on inhibition by Mag and myelin 68 . This discrepancy in results can perhaps be explained by differences in the acute dynamics of growth cone collapse and the chronic dynamics of the cessation of growth that are required for inhibition (BOX 3).…”
Section: R E V I E W Smentioning
confidence: 78%
See 1 more Smart Citation
“…It was shown that inhibition of G i /G o with PERTUSSIS TOXIN blocked myelin-induced growth cone collapse 67 . We, on the other hand, reported that pertussis toxin had no effect on inhibition by Mag and myelin 68 . This discrepancy in results can perhaps be explained by differences in the acute dynamics of growth cone collapse and the chronic dynamics of the cessation of growth that are required for inhibition (BOX 3).…”
Section: R E V I E W Smentioning
confidence: 78%
“…Growth cone collapse is probably the first event in inhibition, and many of the treatments that overcome inhibition of axonal growth also block growth cone collapse/repulsion 68,74 . Mechanistically, collapse and turning are the same, all that differs is the amount of growth cone that is exposed to inhibitors.…”
Section: Box 3 | Mechanisms Involved In Inhibition Of Axonal Growth Vmentioning
confidence: 99%
“…[2][3][4][46][47][48][49] During the past years, different therapies have been proposed that lead to axonal outgrowth after SCI such as SM-216289, 36 neurotrophic factors, 50 soluble Nogo receptors, 51 chondroitinase ABC 49 or cellular transplantation. 52 In particular, SM-216289, a small-molecule inhibitor, showed inhibition of Sema3A functions, including growth cone collapse and chemorepulsion of neurite extension.…”
Section: Discussionmentioning
confidence: 99%
“…39 The role of MAG as an impediment to axonal regeneration is exemplified by in vitro studies in which its immunodepletion from myelin extracts attenuated inhibitory activity. 37 It has since been shown that elevating cAMP can stimulate adult neurons to extend axons on MAG substrates, 40 an effect related to the growth-enhancing effects of conditioning lesions and neurotrophic factor application (see below). Studies in MAG knockout mice have been equivocal, however, since myelin preparations from these mice are still effective in blocking regeneration, and since severed optic nerve and corticospinal tract (CST) axons regenerate no better in MAG knockouts than in wildtype mice.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 99%